2020
DOI: 10.3390/ijerph17197264
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of “Hand Hygiene Fun Month” for Kindergarten Children: A Pilot Quasi-Experimental Study

Abstract: Early childhood is a formative period during which healthy habits are developed, including proper hand hygiene practices. The aim of this quasi-experimental study was to determine the effectiveness of a 4-week series of educational sessions that consider the cognitive developmental stage of children on increasing their knowledge and promoting hand hygiene practices. The intervention group (n = 33) observed the hand hygiene program, whereas another group served as the waitlist control (n = 20). Creative activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, in both situations, the effect of the HHP was statistically significant ( p = 0.001). The findings of this study are similar to many studies which have demonstrated that knowledge level increases after the implementation of hand hygiene training (Lee et al, 2015 ; Mbakaya et al, 2017 , 2019 ; Suen & Cheung, 2020 ; Younie et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…However, in both situations, the effect of the HHP was statistically significant ( p = 0.001). The findings of this study are similar to many studies which have demonstrated that knowledge level increases after the implementation of hand hygiene training (Lee et al, 2015 ; Mbakaya et al, 2017 , 2019 ; Suen & Cheung, 2020 ; Younie et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Kindergarten is the most vulnerable group of children who are yet to fully develop lifesaving skills such as a systematic handwashing technique. This group lacks fully developed fine motor skills (Suen & Cheung, 2020 ). Therefore, it is essential to invest in this age group in order to prevent respiratory infections and diarrhoeal disease which can be fatal and are predominantly transmitted through contaminated hands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations